Aquatic macrophytes of Angola: a preliminary verified checklist - Rafael Somandjinga; Sílvia Quadros; Francisco Maiato; David Goyder (PhytoKeys)
Aquatic macrophytes are photosynthetic macroscopic organisms that grow permanently or periodically submerged or floating on the surface of the water. The aim of this study is to compile a checklist of fresh-water aquatic vascular plant macrophytes occurring in Angola, focusing on their origins, life forms, conservation status and distribution throughout the country. The checklist was compiled through a literature review of previous studies carried out in Angola, herbarium collections and online databases. A total of 526 species of macrophytes in 196 genera and 70 families was recorded. Cyperaceae was the most abundant family, followed by Poaceae, Lentibulariaceae, Lythraceae, Eriocaulaceae, Araceae, Podostemaceae, Hydrocharitaceae, Onagraceae and Plantaginaceae. The highest number of macrophytes was recorded from Huíla Province, followed by Moxico and Cuando Cubango Provinces, respectively, while Lunda Norte, Uíge and Zaire were poorly represented. From the aquatic macrophytes recorded, it was possible to identify the category of origin of 511 species. From these, 472 species are native, 23 introduced and 16 are endemic to Angola and the conservation status of these species was also assessed. The results obtained in this study show that there are still some gaps, especially with regard to the distribution of aquatic macrophytes in Angola, since many species are documented as native, but there is a lack of data on their distribution.